Exploring Proprotein Convertase Subtilisin/Kexin 9 (PCSK9) Autoproteolysis Process by Molecular Simulations: Hints for Drug Design. (9th July 2020) - Sgrignani, Jacopo; Fassi, Enrico M. A.; Lammi, Carmen; Roda, Gabriella; Grazioso, Giovanni
Abstract: Proprotein convertase subtilisin/kexin 9 (PCSK9) is a notable target for the treatment of hypercholesterolemia because it regulates the population of the low‐density lipoprotein receptor (LDLR) on liver cells. The PCSK9 zymogen is a serine protease that spontaneously undergoes a double self‐cleavage step. Available X‐ray structures depict the PCSK9 mature state, but the atomic details of the zymogen state of the enzyme are still unknown. Additionally, why the protease activity of PCSK9 is blocked after the second autoprocessing step remains unclear, as this deviates from other members of the PCSK family. By performing constant‐pH molecular dynamics (MD) simulations, we investigated the protonation state of the catalytic triad of PCSK9 and found that it strongly influences the catalytic properties of the enzyme. Moreover, we determined the final step of the maturation process by classical and steered MD simulations. This study could facilitate the identification of ligands capable of interfering with the PCSK9 maturation process. Abstract : Triad on trial : The protonation state of the catalytic triad of PCSK9 was investigated in constant‐pH MD simulations. Moreover, the last step in the maturation process of the enzyme was also worked out by MD simulations. This study paves the way to designing ligands capable of interfering with the PCSK9 maturation process.